Use of clinoptilolite zeolite to improve efficiency of phosphorus use in acid soils - Hasbullah, Nur Aainaa (2016)
In acid soil of the tropics, soluble P is fixed by aluminium (Al) and iron (Fe). Therefore, efficient management of P fertilizers is critical to meet crops demand and to as well ensure good yield of crops and adequate food supply. In addition, mitigating environmental impacts on water quality and conservation of finite P deposit cannot be over emphasized. Clinoptilolite zeolite as an amendment could be used to mitigate P fixation in acid soils. To this end, a series of experiments were conducted including incubation study, pot trial, and two cycles of Zea mays L. cultivation at Universiti Putra Malaysia, Bintulu Sarawak Campus, Malaysia to improve P use efficiency and to also reduce amount of fertilizers (N, P, and K) use by amending fertilizers with Clinoptilolite zeolite. The three P fertilizers used in this study were a highly soluble P fertilizer (Triple superphosphate, TSP), rock phosphate fertilizers (Christmas Island rock phosphate, CIRP), and Egypt rock phosphate (ERP). The test crop used in this study was F1 maize hybrid (Hibrimas). In the incubation study, different amounts of Clinoptilolite zeolite and fertilizers were evaluated in a controlled environment. The treatments evaluated were: soil alone (T0), 100% fertilizer recommended rates (T1, E1, and C1), 75% fertilizer + 85% Clinoptilolite zeolite based on weight of fertilizer (T2, E2, and C2), 50% fertilizer + 100% Clinoptilolite zeolite (T3, E3, and C3), and 25% fertilizer rate + 115% Clinoptilolite zeolite (T4, E4, and C4). Soil pH was significantly improved with Clinoptilolite zeolite inclusion, whereas soil exchangeable Ca, Mg, Al, and soil acidity were comparable to the recommended rates. Decreased trend in soil exchangeable K, total P, and available P is related to the fertilizers reduction. Generally, P availability and reduction of P fixation (Al-P, Fe-P, Ca-P, reductant-P, and occluded-P) were not significant (inconsistent) in this incubation study, the effect could be different with plant interaction. These aspects were tested in a pot study. Treatments with 25% fertilizer reduction (T2, E2, and C2) were chosen as they showed the closest effects on selected soil chemical properties as compared to the recommended fertilizer rates. The pot study conducted in a controlled environment revealed that amending reduced amounts of fertilizers with Clinoptilolite zeolite had similar effects on selected soil chemical properties and plant performance (dry matter production, nutrients uptake, and nutrients use efficiency). Amount of P fixed was similar to the recommended fertilizer rates thus, explaining the lack of differences in soil P availability, total P, plant dry matter production, nutrients uptake, and nutrients use efficiency despite 25% fertilizer reduction. This suggests the beneficial effect of Clinoptilolite zeolite in reducing P fixation besides improving nutrient uptake and use efficiency. The potential of Clinoptilolite zeolite and its effects on soil chemical properties and Zea mays L. productivity were further determined in a field trial. In the two field trials, maize plants dry matter production, nutrients uptake, and agronomic efficiency were similar regardless of fertilizer rate. Yield of fresh cobs in the first plant cycle showed that the recommended rates of TSP (T1), ERP (E1), and CIRP (C1) were 17 t ha-1, 9.1 t ha-1, and 8.8 t ha-1, respectively. Reducing fertilizers by 25% but with Clinoptilolite zeolite resulted in comparable fresh cob yield as that of the recommended fertilizer rates. In the second plant cycle, there was an increase in the fresh cob yield. Plots with TSP and the treatments with fertilizers reduction and Clinoptilolite zeolite yielded 25 t ha-1 and 22 t ha-1 fresh cobs, respectively. Application of ERP resulted in 11.6 t ha-1 in both recommended and reduction treatments whereas CIRP recorded 17.5 t ha-1 for the recommended treatment and 15 t ha-1 fresh cobs for the reduced fertilizer rate. Clinoptilolite zeolite inclusion in the first plant cycle neither increased soil pH, P availability, and basic cations nor reduced P fixation, soil acidity, and exchangeable Al. The aforementioned results remained similar in the second cycle of maize cultivation except for pH. Inclusion of Clinoptilolite zeolite increased soil pH as the recommended fertilizer rates. Although Clinoptilolite zeolite inclusion neither improved P availability nor reduced P adsorption, similar retention and availability of P despite 25% fertilizer reduction was observed. This suggests that Clinoptilolite zeolite enhanced-exchange mechanism, retention of basic cations from leaching, RP dissolution, efficient use of fertilizer thus, producing desirable yield. Clinoptilolite zeolite is beneficial and could be used to reduce the amount of N, P, and K fertilizers use in Zea mays L. cultivation on acid soils besides reducing the risk of environmental pollution. Perhaps, in a long term application, selected soil chemical properties could be significantly improved through the conditioning effects of Clinoptilolite zeolite. Clinoptilolite zeolite application reduced leaching losses of Ca and Mg, hence, the similar results obtained in this study regardless of treatment. Availability of N, P, K, and Fe in soil significantly reduced with Clinoptilolite zeolite application with 25% fertilizer reduction. As proven in the two cycles of maize cultivation, the use of Clinoptilolite zeolite in agriculture is beneficial as it can be used to reduce the unbalanced use of N, P, and K fertilizers of Zea mays L. and related crops cultivated on acid soils. Besides, it can be used to minimize environmental pollution due to excessive use of chemical fertilizers and mobility of toxic elements. Economic viability analysis for including Clinoptilolite zeolite in maize cultivation revealed that the total cost of production reduced with Clinoptilolite zeolite adoption due to elimination of liming. Benefit cost-ratio for the recommended fertilizer rates was 1.69 whereas Clinoptilolite zeolite inclusion increased benefit cost-ratio (1.83-1.84). Thus, adoption of Clinoptilolite zeolite in reduced amount of fertilization was found to be economically feasible as it not only gives higher profit in return but hopefully could also promote sustainability of agricultural productivity and soil fertility.